An Evaluation of Phenolic Compounds, Carotenoids, and Antioxidant Properties in Leaves of South African Cultivars, Peruvian 199062.1 and USA's Beauregard - Phahlane, Charmaine J.; Laurie, Sunette M.; Shoko, Tinotenda; Manhivi, Vimbainashe E.; Sivakumar, Dharini (Frontiers in Nutrition, 2021)
In this study, leaves of sweet potato cultivars from South Africa, (‘Ndou’, ‘Bophelo’, ‘Monate’ and ‘Blesbok’), ‘Beauregard’ a sweet potato cultivar from the USA, and a Peruvian cultivar ‘199062.1’ were analysed using UPLC/QTOF/MS and chemometrics, with the aim of characterizing the locally developed sweet potato cultivars and comparing them with already well-known established varieties on the market. A set of 13 phenolic compounds was identified. A partial least squares discriminant analysis, a hierarchical cluster analysis, and variables importance in projection were used to successfully distinguish sweet potato varieties based on their distinct metabolites. Caffeic acid enabled to distinguish cluster 1 leaves of varieties ('Beauregard' and 'Ndou') from cluster 2 (‘199062.1’, ‘Bophelo’, ‘Monate’, and ‘Blesbok’). The leaves of ‘Bophelo’ contained the highest concentrations of rutin , quercetin 3-O-galactoside, 3-caffeoylquinic acid (3-CQA), (5-CQA), 1,3 dicaffeoylquinic acid (1,3-diCQA), 1,4-diCQA and 3,5-diCQA. Further, Bophelo leaves showed the highest antioxidant activities (FRAP 19.69mM TEAC g-1, and IC50 values of (3,51 mg ml-1 and 3.43 mg ml-1) for DPPH and ABTS respectively compared to the other varieties. Leaves of 'Blesbok' contained the highest levels of β-carotene (10.27 mg kg-1) and zeaxanthin (5.02 mg kg-1) on dry wight basis compared to all other varieties. This study demonstrated that the leaves of local cultivars 'Bophelo' and 'Blesbok' have the potential to become functional ingredients for food processing.